2017
DOI: 10.1111/sji.12616
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Circulating Tfr/Tfh Ratio in Primary biliary cholangitis

Abstract: Follicular helper T (Tfh) cells and follicular regulatory T (Tfr) cells are critical for the development and maintenance of germinal centre (GC) and humoral immune responses. Accumulating evidence has demonstrated that the dysregulation of either Tfh cells or Tfr cells contributes to the pathogenesis of autoimmune diseases. We aim to investigate the roles of circulating Tfh cells and circulating Tfr cells in the pathogenesis of primary biliary cholangitis (PBC). A total of 34 patients with PBC and 27 health in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 30 publications
1
21
1
Order By: Relevance
“…Although TFR cells are known to be important regulators of autoimmune responses in human, the precise role of TFR cell in the pathogenic processes of AIH remains unclear. This study showed sufficient evidence that dysregulated between TFR and TFH cells contribute to the immunopathological process in AIH.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Although TFR cells are known to be important regulators of autoimmune responses in human, the precise role of TFR cell in the pathogenic processes of AIH remains unclear. This study showed sufficient evidence that dysregulated between TFR and TFH cells contribute to the immunopathological process in AIH.…”
Section: Discussioncontrasting
confidence: 98%
“…Several studies have showed that abnormal TFR cells activity might cause the destruction of immune tolerance and thereby lead to the immunopathogenesis of autoimmune diseases . Additionally, like TFH cell, TFR cells are also present in the peripheral circulation, the levels of which are directly correlated with a variety of human immunological disorders, such as primary biliary cholangitis (PBC) and multiple sclerosis(MS) . However, to the best of our knowledge, there are no reports of circulating TFR cells in patients with newly diagnosed AIH.…”
Section: Introductionmentioning
confidence: 99%
“…Systemic AIDs involve rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), Sjögren's syndrome (SS), ankylosing spondylitis (AS), IgG4‐related disease (IgG4‐RD) and common variable immune deficiency (CVID) . Organ‐specific AIDs involve multiple sclerosis (MS), myasthenia gravis (MG), Hashimoto's thyroiditis (HT), primary biliary cholangitis (PBC), type 1 diabetes (T1D) and ulcerative colitis (UC) . It is also demonstrated that when the regulatory capacity of Tfr cells is impaired, the expansion of Tfr cells is accompanied by the development of autoimmunity in mice …”
Section: Tfr Cells In Human Diseases and Animal Modelsmentioning
confidence: 99%
“…Decreased cTfr cells and increased cTfh cells are found in patients with PBC . Meanwhile, both ICOS + cTfr cells and CTLA‐4 + cTfh cells are increased, and the ratio of cTfr/cTfh is inversely correlated with disease progression, drug response and the level of serum IgM.…”
Section: Tfr Cells In Human Diseases and Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation